Biohybrids: Biohybrid Janus Motors Driven by Escherichia coli (Adv. Mater. Interfaces 2/2016). Issue 2 (21st January 2016) - Stanton, Morgan M.; Simmchen, Juliane; Ma, Xing; Miguel‐López, Albert; Sánchez, Samuel
Abstract : In article number 1500505, S. Sánchez and co‐workers describe the fabrication of motile biohybrid swimmers. Escherichia coli adhere to metal caps on polystyrene (PS) Janus particles. The regulated cell adhesion allows the PS surface to be utilized for drug attachment, creating a multifunctional system. E. coli demonstrate the ability to carry multiple cargo loads, while maintaining high cell viability and proliferation.